IMPLEMENTASI SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN TENAGA KESEHATAN TERBAIK MENGGUNAKAN METODE WEIGHTED PRODUCT - Ikhsanuddin, Muhammad Nur; Srirahayu, Agustina; Muhammad, Nibras Faiq (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
This research aims to develop a web-based decision support system (DSS) for selecting the best healthcare professionals using the Weighted Product (WP) method. The system is designed to assist hospital institutions in determining the best healthcare professionals based on the criteria set by the Minister of Health Regulation of the Republic of Indonesia Number 23 of 2016. The research was conducted at CV Sumber Solusi Bersama, focusing on the development of a Hospital Management System. The WP method was chosen for its ability to handle complex multi-criteria decision-making. The results of the research indicate that the developed system can improve efficiency and accuracy in the process of selecting the best healthcare professionals, thereby enhancing the quality of healthcare services in hospitals.